Using Social Network Analysis to study Knowledge Transfer in Rural Destination: A Case Study of Nangang, China - Shiqi Liu, Mingfang Zhu, Yuan Zhang (Forest Chemicals Review, 2022)
The tourism industry can benefit from knowledge management, especially in knowledge transfer and knowledge-based innovation. Knowledge generation, dissemination, and acquisition in tourism were more complex, informal, and sometimes not well-planned.  Therefore, it is important to understand the process and mechanisms through which knowledge is shared and transferred in tourism system. To address it, this paper applies SNA (social network analysis) to identify the major actors in knowledge networks in a rural tourism destination located in north-east China. Empirical findings show that sector of culture and tourism of local government and government industry collaborations can be the leading hub of ‘administered knowledge networks’ – understood as efficient knowledge governance arrangements – in which a wide variety of actors, including public sectors, enterprises, local community and pressure groups play complementary roles depending on the nature of the interactions (formal transfer versus informal exchange flows). These structures are found to be fundamental for the functioning of rural destination knowledge sharing.